(untitled) (Research, Society and Development, 2021)
Objective: To know the perception of nursing graduates about training for work in the area of oncology. Method: Exploratory research, qualitative approach, developed in an Institution of High Complexity in oncology in the West region of Paraná. Data collection took place from April to May 2019, through semi-structured interviews, with 35 nurses being employed in the care of cancer patients. Thematic data analysis was carried out. Results: Three thematic units were elaborated: Challenges in Oncology, Training to operate in Oncology and specialization in Oncology. The nurses pointed out the difficulties to perform this care and the lack of contact with the theme during graduation, seeking specialization to support knowledge. Interviewees’ respondents propose how the topic should be addressed in the curriculum. Conclusion: It is necessary in order to expand the discussion on oncology during the nurse’s graduation.